WANPRESTASI TERTANGGUNG PADA PERJANJIAN ASURANSI JIWA (Studi Pada PT. Prudential Life Assurance Medan) - Luther Sembiring, Marthin (JURNAL CIVIL LAW USU, 2013)
Abstract : If in one agreement, one person do not execute what they have been dealing, then the other can pursue that one person with a number of compentation (punitive damages). In an insurance agreement has been arrangedthe certainty about the right and duty of the member in the psyche insurance policy that was been a basic of psyche insurance agreement. Sometimes, there is a problem in the realization of insurance agreement when Tertanggung don’t pay, even they stop their duty in paying the premi with any variation reason. Kata Kunci : Wanprestasi, Perjanjian, Asuransi Jiwa